PENGARUH LOKASI, INOVASI PRODUK, DAN CITA RASA TERHADAP KEPUTUSAN PEMBELIAN PADA ELEVEN CAFE DI KOTA BENGKULU - Elvina Endah Puspa Wulandari (UM. Bengkulu, 2021)
This study aims to determine the effect of location, product innovation, taste image as well on customersâ€™ purchasing decisions at Eleven Cafe of Bengkulu City, and find out the most dominant factors that influence purchase decisions of three variables above. The method of this research used quantitative analysis by taking up data through observation and questionnaires toward 96 respondents with Accidental Sampling method. The results of study obtained that multiple linear regression test by using SPSS program; Y = 0.193 + 0.262 (X1) + 0.168 (X2) + 0.249 (X3). The coefficient of determination (R2) Adjusted R Square value was 0.881 or 88.1%, this means that together location (X1), product innovation (X2) and taste image (X3) contributed 88.1% to influence the purchasing decision (Y) at Eleven Cafe of Bengkulu City. While, hypothesis testing t_test showed that the location variable (X1) was 0.002 <0.050, the product innovation variable (X2), 0.012 <0.050 and the taste image variable (X3) obtained 0.000 <0.050. All of these variables partially have an effect on purchasing decisions. Furthermore, F_test showed that the location (X1), product innovation (X2), and taste image (X3) have influenced the purchase decision (Y) with a significance level <0.050, it means Ho was refused, Ha accepted.Â Keywords: Location, Product Innovation, Taste Image, Purchasing Decisions.